Editorial: Left Behind Regions in Europe and Beyond (Transactions of the Association of European Schools of Planning, 2022)
The causes and impacts of new and enduring regional inequalities have been much debated in many regions and countries around the globe over the past decade. This has been reflected in public and political discourse with references to and imaginaries of so-called ‘forgotten’ or ‘left behind’ regions and peripheral territories. Discourses and movements of political discontent have sparked off renewed debates on uneven development and the experience of left-behind places, which struggle with persistent social and economic challenges and might appear to be seen as ‘places that don’t matter’ (Rodríguez-Pose, 2018).